2014
DOI: 10.1039/c3nr04960d
|View full text |Cite
|
Sign up to set email alerts
|

APTS and rGO co-functionalized pyrenated fluorescent nanonets for representative vapor phase nitroaromatic explosive detection

Abstract: For the first time, flexible PVP/pyrene/APTS/rGO fluorescent nanonets were designed and synthesized via a one-step electrospinning method to detect representative subsaturated nitroaromatic explosive vapor. The functional fluorescent nanonets, which were highly stable in air, showed an 81% quenching efficiency towards TNT vapor (∼10 ppb) with an exposure time of 540 s at room temperature. The nice performance of the nanonets was ascribed to the synergistic effects induced by the specific adsorption properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Recently, for the detection of subsaturated nitroaromatic explosive TNT vapor, Dou's group [33] designed PVP(polyvinylpyrrolidone)/pyrene/APTS/graphene oxide (rGO) fluorescent nanonets (Fig. 2c) with an 81% quenching efficiency, LOD of 10 ppb and an exposure time of 540 s at room temperature.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Recently, for the detection of subsaturated nitroaromatic explosive TNT vapor, Dou's group [33] designed PVP(polyvinylpyrrolidone)/pyrene/APTS/graphene oxide (rGO) fluorescent nanonets (Fig. 2c) with an 81% quenching efficiency, LOD of 10 ppb and an exposure time of 540 s at room temperature.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…For example, Guo et al . prepared poly(vinylpyrrolidone)/pyrene/3‐aminopropyltriethoxysilane/reduced graphene oxide nanonets by electrospinning from their blends and reported that the nanonets gave quenching efficiency of 81% toward TNT vapor (10 ppb) within 540 s at room temperature …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many methods have been developed to detect TNT and DNT, such as, fluorescence sensing, 3 mass spectrometry, 4,5 electrochemical testing, 6 and gas and liquid chromatography. 18,19 For example, Guo et al 20 prepared polyvinylpyrrolidone/ pyrene/3-aminopropyltriethoxysilane/reduced graphene oxide nanonets by electrospinning from their blends and reported that the nanonets showed a quenching efficiency of 81% toward TNT vapor within 540 s at room temperature. Fluorescence sensing seems to be a facile and promising method according to the criteria mentioned above.…”
Section: Introductionmentioning
confidence: 99%